Discourse features of english texts introducing museums - Nguyễn Thị Thúy Hằng (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study is aimed at examining discourse features of English Texts Introducing Museums (ETIMs). The data for analysis in this thesis are 160 samples of ETIMs collected from the official websites of museums in London, England. The study was conducted based on the combination of a variety of methods such as descriptive, analytic and inductive ones. The study focused on analyzing discourse features of ETIMs in terms of their layout, syntactic structures, lexical choices and cohesive devices. The findings of this study were clearly presented based on survey of 160 English Texts Introducing Museums. With regard to layout, the Headline, the Slogan, the Illustration and the Body Copy are the four main components of ETIMs. Furthermore, relative clauses, the passive voice and imperative sentences are the most striking structures in ETIMs. In addition, descriptive adjectives, noun phrases as proper names, addressing terms and personal pronouns are prominent lexical choices in ETIMs. Finally, the investigation of cohesive devices revealed that reference, conjunction, repetition, ellipsis and synonym are the devices employed with high frequencies. On the basis of the findings, some practical implications for teaching and learning English were suggested. The study provides an insight into discourse features of texts in general as well as English Texts Introducing Museums in particular. It is hoped that the findings of this thesis will probably be useful for those who are interested in texts, especially English Texts Introducing Museums.